Pediococcus pentosaceus Enhances Host Resistance Against Pathogen by Increasing IL-1β Production: Understanding Probiotic Effectiveness and Administration Duration - Shan, Chengjie; Li, Miao; Liu, Zhu; Xu, Rong; Qiao, Fang; Du, Zhen-Yu; Zhang, Mei-Ling (Frontiers in Immunology, 2021)
Probiotic administration is a potential strategy against enteric pathogens infection in either clinical treatment or animal nutrition industry, but the administration duration of probiotics varied and the underlying mechanisms remain unclear. A strain (YC) affiliated to Pediococcus pentosaceus, a commonly used probiotic, was isolated from fish gut and the potential role of YC against Aeromonas hydrophila was detected in zebrafish. We found that 3- or 4-week YC administration (YC3W or YC4W) increased the resistance against A. hydrophila while 1- or 2-week treatment (YC1W or YC2W) did not. To determine the possible reason, intestinal microbiota analysis and RNAseq were conducted. The results showed that compared with CON and YC1W, YC4W significantly increased the abundance of short-chain fatty acids (SCFAs) producing bacteria and elevated the gene expression of nlrp3. Higher butyrate content and enhanced expression of IL1β were subsequently found in YC4W. To identify the causal relationship between butyrate and the higher pathogen resistance, different concentrations of sodium butyrate (SB) were supplemented. The results suggested that 10 mmol/kg SB addition mirrored the protective effect of YC4W by increasing the production of IL-1β. Furthermore, the increased IL-1β raised the percentage of intestinal neutrophils which endued the zebrafish with A. hydrophila resistance. In vivo knockdown of intestinal il1b eliminated the anti-infection effect. Collectively, our data suggested that the molecular mechanism of probiotics determined the administration duration which is vital for the efficiency of probiotics. Promoting host inflammation by probiotic pretreatment is one potential way for probiotics to provide their protective effects against pathogens.